Development of bottled pickled red pepper (Capsicum annuum) - Valdez, Erlinda A.; Gatchalian, Miflora M. (1973.)
The study was conducted to develop a standard procedure for cannin sweet-sour pickled pepper which could have consumer acceptance. This involved three main sections, namely: standardization of procedure, development of recipe specifications and finally formulation of a standardized recipe and procedure. The final product revealed that blanching the peppers for 3 minutes was sufficient to "cook" the peppers to prevent discoloration and other enzymatic changes. Droppong in ice water after blanching contributed to a better product in terms of texture. The use of 0.5% alum as concentration of chosen firming agent, a 40B sugar-vinegar mixture using coconut vinegar produced the most acceptable product in terms of color, odor, texture and flavor. Such characteristic were measured by the 9-point hedonic rating scale which showed that the product is "moderately" acceptable. Acceptability was further supported by results and descriptive tests which showed that the product was firm, had an attractive red color, characteristic pickle odor and just the right sweet-sour blend.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Peppers; Vegetables -- Preservation